SPATIAL STUDY OF SEISMIC HAZARD USING CLASSICAL PROBABILISTIC SEISMIC HAZARD ANALYSIS (PSHA) METHOD IN THE KENDARI CITY AREA - Purba, Joshua; Restele, La Ode; Hadini, La Ode; Usman, Ida; Hasria, Hasria; Harisma, Harisma (Indonesian Physical Review, 2024)
Kendari City is an area prone to earthquakes because it is in a seismic zone dominated by local faults such as the Lawanopo Fault, Kendari Fault, Buton Fault, Tolo Thrust and Matano Fault, as evidenced by significant seismic events like those in 2011 and 2022. The earthquake in 2011, with a magnitude of 6.0, struck Kolono District, South Konawe Regency, while the 2022 earthquake, registering a magnitude of 5.2, occurred in the sea approximately 5 km north of Soropia, Konawe Regency. With seismic activity such as the 2011 and 2022 earthquakes causing significant damage, understanding seismic hazards is critical. The research stage starts from Hazard Analysis using the Classical Probabilistic Seismic Hazard Analysis (PSHA) method to produce a hazard map that presents the distribution of peak ground acceleration on the surface, at periods 0 seconds (PGA), SA (T= 0.2 seconds) and SA (T= 1.0 seconds) for probabilities of exceedance 10% and 2% in 50 years, respectively. Classical Probabilistic Seismic Hazard Analysis (PSHA) processing uses OpenQuake Engine software. The analysis results show that the PGA value in Kendari City on the surface ranged from (0.49 - 0.68 g and 0.79 - 1.17 g), SA at T= 0.2 seconds (1.10 - 1.53 g and 1.74 - 2.09 g), and SA at T= 1 second (0.64 - 0.93 g and 1.35 - 1.91 g). This result indicates the potential for significant damage and shocks.